THE SUGGESTOPEDIA METHOD TO IMPROVE STUDENTS’ WRITING SKILL OF NARRATIVE TEXT - Rodifah Rodifah; Ina Rohiyatussakinah; Ida Nuraida; Fadilla Oktaviana (Journal of English Language Teaching and Literature (JELTL), 2023)
The background of the researcher to analyze students' ability in writing narrative texts by analyzing several aspects of writing skills in the form of content, organizational ideas, grammar, vocabulary and mechanical punctuation. The aims of the research are to find out suggestopedia method able to increase students’ writing of narrative text and to find out studensts’ interest using suggestopedia method. The method used in this research was classroom action research. The research procedure includes cycle I and cycle II using research instruments in the form of observations and tests. This research was conducted at SMAN 1 BINUANG class XI MIA 1. Minimum completeness criteria (KKM) value is 70. The results of research on student pre-test got the average score of 41 and cycle 1 got average score of 68 and have not reached KKM. Therefore, treatment was carried out to be able to increase the students score by doing learning used suggestopedia method in cycle 2 obtained average score of 79 has reached KKM. Then, the action hyphotesis could be said that the suggestopedia method improve students’ writing narrative text and make students interested in learning. Futhermore, it could be concluded that the results of these scores prove that one of the supporting factors to improve the student learning outcomes is the used of appropriate learning methods and can be well received by students such as the suggestopedia method.